Mechanical, optical, and thermal properties of boron carbon nitride-filled polyvinyl alcohol composites for ultraviolet shielding applications - Sazci, Oguler; Adiguzel, Aysegul Cigdem; Ugraskan, Volkan (ELSEVIER, 2026)
Polyvinyl alcohol (PVA) is an environmentally benign polymer with good optical transparency and processability; nevertheless, its weak ultraviolet (UV) shielding capability and modest mechanical and thermal stability limit its widespread application. In this study, boron carbon nitride (BCN) was added to a PVA matrix at ultralow filler loadings (0.1-1.0 wt%) to create multifunctional composite films with improved performance. Structural investigations confirmed the uniform dispersion of BCN within the PVA matrix and showed the creation of strong hydrogen bonding interactions that disrupt PVA crystallinity. Optical studies showed a progressive reduction of the direct and indirect optical band gaps, which decrease from 5.16 to 4.67 eV and 4.79 to 4.61 eV, respectively, accompanied by a significant increase in UV-A and UV-B absorption while maintaining visible-light transparency. Thermal investigations showed that the strong interfacial contacts between the BCN and PVA chains improve thermal stability and modify melting behavior. Mechanical testing revealed remarkable reinforcement efficiency, with elastic modulus increasing by 219% and yield strength increasing by 94% at just 1 wt% BCN loading. These findings showed that BCN-filled PVA composites combine effective UV shielding with significantly improved mechanical and thermal properties, making them viable candidates for advanced flexible UV-shielding materials.
Keywords: Polyvinyl alcohol; Boron carbon nitride; Composite; UV-shielding; NANOCOMPOSITES; FILMS; Chemistry